What is the sum of the coefficients?

Algebra Level pending

Determine the value of the sum of the coefficients in the expansion of

g ( x ) = ( x + 2 ) 3 ( x 2 + 2 x + 1 ) 4 g(x)={ (x+2) }^{ 3 }{ ({ x }^{ 2 }+2x+1) }^{ 4 }


The answer is 6912.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Geoff Taylor
Dec 24, 2017

The sum of the coefficients can be determined by letting x = 1 This gives g ( 1 ) = ( 1 + 2 ) 3 ( 1 2 + 2 × 1 + 1 ) 4 = 6912 g(1)={ (1+2) }^{ 3 }{ ({ 1 }^{ 2 }+2\times 1+1) }^{ 4 }=6912

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...